Deprivation Has Inconsistent Effects on Delay Discounting: A Review - Downey, Haylee; Haynes, Jeremy M.; Johnson, Hannah M.; Odum, Amy L. (Frontiers in Behavioral Neuroscience, 2022)
Delay discounting, the tendency for outcomes to be devalued as they are more temporally remote, has implications as a target for behavioral interventions. Because of these implications, it is important to understand how different states individuals may face, such as deprivation, influence the degree of delay discounting. Both dual systems models and state-trait views of delay discounting predict that deprivation may result in steeper delay discounting, but early experiments examining the effect of deprivation on delay discounting provided mixed results. Despite early inconsistencies, researchers have sometimes asserted that deprivation increases delay discounting, with few qualifications. The aim of this review was to determine what effect, if any, deprivation has on delay discounting. We considered many kinds of deprivation, such as deprivation from sleep, drugs, and food in humans and nonhuman animals. For 23 studies, we analyzed the effect of deprivation on delay discounting by computing effect sizes for the difference between delay discounting in a control, or baseline, condition and delay discounting in a deprived state. We discuss these 23 studies and other relevant studies found in our search in a narrative review. Overall, we found mixed effects of deprivation on delay discounting. The effect may depend on what type of deprivation participants faced. Effect sizes for deprivation types ranged from small for sleep deprivation (Hedge’s gs between -.21 to .07) to large for opiate deprivation (Hedge’s gs between .42 to 1.72). We discuss possible reasons why the effect of deprivation on delay discounting may depend on deprivation type, including the use of imagined manipulations and deprivation intensity. The inconsistency in results across studies, even when comparing within the same type of deprivation, indicates that more experiments are needed to reach a consensus on the effects of deprivation on delay discounting. A basic understanding of how states affect delay discounting may inform translational efforts.